Investigating the Effect of Investors' Behavior and Management on Stock Returns - Kazem Shamsadini (Ph.D) (Shahid Bahonar University of Kerman, 2018)
The purpose of the present study was to investigate the effects of behavioral variables such as managerial overconfidence, herding behavior and investor sentiment on stock returns. To this end, using the data of 75 companies listed in Tehran Stock Exchange during the seven-year period of 2010-2016, the index of managerial overconfidence, herding behavior of investors and the investor sentiment are calculated and their impact on stock returns were examined. To analyze the data and test the hypotheses, the linear regression model has been used by estimating generalized least squares (EGLS). Evidence and empirical results of the research showed that the behavioral variables studied in the research have a reciprocal and significant effect on the stock returns of the companies. Therefore, the greater the degree of reliance on managerial overconfidence, investors’ herding behavior and investor sentiment, the more inverse effect on the companies’ stock returns, we will see.